If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -10 = -6x + 3 Reorder the terms: -10 + 4x = -6x + 3 Reorder the terms: -10 + 4x = 3 + -6x Solving -10 + 4x = 3 + -6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6x' to each side of the equation. -10 + 4x + 6x = 3 + -6x + 6x Combine like terms: 4x + 6x = 10x -10 + 10x = 3 + -6x + 6x Combine like terms: -6x + 6x = 0 -10 + 10x = 3 + 0 -10 + 10x = 3 Add '10' to each side of the equation. -10 + 10 + 10x = 3 + 10 Combine like terms: -10 + 10 = 0 0 + 10x = 3 + 10 10x = 3 + 10 Combine like terms: 3 + 10 = 13 10x = 13 Divide each side by '10'. x = 1.3 Simplifying x = 1.3
| (N+4)*5=65 | | 79-(5x+16)=5(x+6)+x | | g(x)=2x-1 | | 3x^2-17x-12=0 | | 4x-7=3(2+1) | | 6:?x10/2 | | 9-4x[3-(7-2)/2] | | 8X(2X-3)-4X(4x-1)=40 | | 8x+6y=4 | | 100a-a^2-2484=0 | | 10m+6=56 | | 1-8x-7x=16 | | 4x-8=2x+19 | | 0.75y=9 | | 4x^2+9x^2=0 | | 4x*7/12x | | 2x^3+24x=y | | 42x^2-33x=0 | | 3v^5-192v^2= | | 7(-6x-4)= | | 3ln(4x-1)=9 | | ln(2x+1)+ln(x-3)=ln(x+5) | | 2x-8=38 | | 1=x/9 | | 9=-6+5v | | 0.3=20 | | x^2-8x+y^2+10y=-1 | | 1/3=20 | | y=-.005x^2+0.5x | | 205=-u+287 | | 1.6m-4.8=1.6m | | -3(x-3)-4(x+4)= |